A model for carbon incorporation from trimethyl gallium in chemical vapor deposition of gallium nitride. Issue 4 (7th January 2016) - Danielsson, Örjan; Li, Xun; Ojamäe, Lars; Janzén, Erik; Pedersen, Henrik; Forsberg, Urban
Abstract : Carbon doping during CVD of GaN semiconductor materials is modeled using ab initio quantum chemical calculations and computational fluid dynamics. Abstract : Semi-insulating buffer layers are utilized to prevent leakage currents in Gallium Nitride (GaN) high power semiconductor devices. To make the GaN material semi-insulating, it can be doped with carbon. Carbon is inherently present in the process for producing GaN thin films by chemical vapor deposition (CVD), through the use of trimethyl gallium (TMGa) as a precursor. TMGa decomposes in the gas phase, releasing its methyl groups, which act as a carbon source for doping. It is previously known that carbon doping levels can be controlled by tuning CVD process parameters, such as temperature, pressure and precursor flow rates. However, the mechanism for carbon incorporation from TMGa is not yet understood. In this paper, a reactor independent model for predicting carbon incorporation from TMGa in GaN layers grown by CVD is proposed. The model is based on ab initio quantum chemical calculations of molecular adsorption and reaction energies. Computational Fluid Dynamics, including a chemical kinetic model for the decomposition of the precursors and reactions in the gas phase, is used to calculate gas mixture composition under realistic process conditions. These results are used together with the proposed model to obtain carbon doping concentrations as well as growth rates, varying inlet NH3 /TMGa ratios (157–625) and temperature (800–1100 °C). The model predictions are then correlated with measurements with good agreement. It is concluded that the contribution of gallium to the GaN layer shifts from GaCH3 at low temperatures to atomic Ga at higher temperatures. In the same way there is a shift in carbon doping contribution, from CH3 at low temperatures to C2 H x at higher temperatures.